Organization of simulation and game activities in history lessons in senior classes (Pedagogy of Higher and Secondary Education, 2011)
The article reveals the essence of play in high school history lessons. The author presents examples of practical application of some games and proved the effectiveness of simulation-gaming activities.
Keywords: game activity and training history; age-graders